25 Advance care planning in patients with systemic right ventricular failure. (4th June 2021) - Copley, Alice; Gardner, Sarah; Joy, Eleanor; Oliver, James; English, Kate; Cullington, Damien; Gopaul, Karina
Abstract : Introduction: Patients with transposition of the great arteries (ccTGA) and patients with transposition of the great arteries who had palliative surgery (Mustard/Senning procedures) often have progressive functional deterioration of the systemic right ventricle (sRV) and develop heart failure from the third or fourth decade of life. 1 End stage heart failure requires an integrated approach and advance care planning (ACP) 2 with ACHD cardiologists working alongside specialist heart failure and palliative care teams. We describe current practice with regards to ACP and palliative care referrals in patients with sRV at a tertiary referral centre. Methods: Patients with ccTGA, Mustard or Senning procedures who were under active follow up from 2016 to 2021 were retrospectively analysed (n=122). Clinical and echocardiographic data were extracted from hospital electronic records and screened for factors which should prompt the consideration of palliative care referral and ACP as specified in prior guidance. 2 These were; an episode of decompensation within 6 months despite optimal medical therapy, malignant arrhythmias, cardiac cachexia, frequent or continued intravenous therapies, poor quality of life (QoL), or progressive functional decline with dependence in activities of daily living and New York Heart Association (NYHA) IV symptoms. Results: Baseline information is summarised in table 1 . 7 patients had ACP ( figure 1 ). 2 occurred during hospital admission in NYHA III patients with more than 1 episode of decompensation in 6 months despite optimal medical therapy, need for frequent intravenous therapy and chronic poor QoL. Cardiopulmonary resuscitation, implanted cardiac defibrillator deactivation and future care preferences were discussed. 5 patients had ACP as an outpatient who were NYHA I or II, which were patient initiated (n=3) and clinician initiated in response to progressive functional decline (n=1) and no identifiable prompt (n=1). 5 patients died during the data collection period (median age 41 years), 1 of which had advanced heart failure, discussed ACP and was referred to palliative care. 2 patients did not have ACP or palliative care input, however did meet the criteria for doing so ( table 2 ). Conclusions: In our cohort of patients with sRV, the majority of patients are NYHA class I and II with mild or moderately impaired sRV function. ACP occurred in 60% of patients with NYHA III symptoms. The timing of ACP or palliative care referral can be challenging due to the subjective under reporting of symptoms and risk of sudden death in this group. ACP discussions in the outpatient setting occurred irrespective of NYHA class severity and were mostly patient initiated. Early discussion is advocated in light of recent guidance 3 recommending staged ACP to those who express an interest, or concurrently with planning interventions such as device implantation, heart transplant assessment, catheter interventions or cardiac surgery. Conflict of Interest: None References: Brida M, Diller GP, Gatzoulis MA. Systemic right ventricle in adults with congenital heart disease. Circulation 2018;137 :508–518. Jaarsma T et al . Advanced heart failure study group of the HFA of the ESC. Palliative care in heart failure: a position statement from the palliative care workshop of the Heart Failure Association of the European Society of Cardiology. Eur J Heart Fail 2009;11 (5):433–43 Schwerzmann M et al . Recommendations for advance care planning in adults with congenital heart disease: a position paper from the ESC Working Group of Adult Congenital Heart Disease, the Association of Cardiovascular Nursing and Allied Professions (ACNAP), the European Association for Palliative Care (EAPC), and the International Society for Adult Congenital Heart Disease (ISACHD). European Heart Journal 2020;41 (43):4200–4210.